Composite electrospun scaffold containing decellularized amniotic matrix for pelvic organ prolapse. (15th November 2021) - Yang, Deyu; Fang, Zhou; Kang, Rui; Liu, Kehai
Graphical abstract: Highlights: First design of electrospun scaffolds composed of degradable polymers and dHAM for POP. PCL, PLGA and dHAM in scaffolds are complementary in physical and biological properties. Indirect and direct cell tests using MSCs proved that new materials were cytocompatibility. Abstract: Pelvic organ prolapse (POP) is a frequent chronic illness, which severely affects women's quality of life. In this work, four composite electrospun scaffold were developed for POP using decellularized amniotic matrix (dHAM) and biocompatible polymers like poly(ε-caprolactone) (PCL) and poly(lactide-co-glycolide) polymers (PLGA). Tests to assess the physicochemical characterizations of the novel scaffold were performed. The results showed that scaffolds had good hydrophilicity, suitable degradation time and mechanical properties for pelvic floor regeneration. Cell tests with human umbilical cord mesenchymal stem cells (hUC-MSCs) showed that scaffolds were non-cytotoxic. In conclusion, composite electrospun scaffold containing dHAM showed promising potential for POP.